2020
DOI: 10.1111/aji.13365
|View full text |Cite
|
Sign up to set email alerts
|

IL1B triggers inflammatory cytokine production in bovine oviduct epithelial cells and induces neutrophil accumulation via CCL2

Abstract: Problem The oviduct is essential for reproduction. We previously showed that oviduct epithelial cells (OECs) isolated from aged cows expressed higher levels of inflammatory cytokines, including interleukin (IL) 1A and IL1B. In addition, aging is associated with tissue dysfunction and cellular senescence via a senescence‐associated secretory phenotype (SASP) and immune cell accumulation. We investigated whether IL1A or IL1B causes SASP production, cellular senescence, and inflammatory responses in bovine OECs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Some of the myeloid genes in our model have been shown to regulate multiple immune cells by previous studies. IL1B, belonging to the IL1 system, can drive senescence-associated secretory phenotypes (SASPs), which may affect immune cell activation and induce neutrophil accumulation ( 76 , 77 ). In addition, the shed ectodomain of LYVE1 expressed on M2 cells inhibited cancer cell proliferation ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the myeloid genes in our model have been shown to regulate multiple immune cells by previous studies. IL1B, belonging to the IL1 system, can drive senescence-associated secretory phenotypes (SASPs), which may affect immune cell activation and induce neutrophil accumulation ( 76 , 77 ). In addition, the shed ectodomain of LYVE1 expressed on M2 cells inhibited cancer cell proliferation ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other than mediating macrophage polarization, considerable studies report that IL-1β may be involved in the senescence of several types of cells, including vascular smooth muscle cells 23 , astrocytes 24 , bovine oviduct epithelial cells 25 , mature chondrocytes 26 , etc. Recently, several studies have shown positive correlations between senescent cell accumulation and fibrosis in kidneys during ageing 27 29 and disease 30 32 .…”
Section: Resultsmentioning
confidence: 99%
“…But here, we also have a question whether only cancer-related genes have such a pattern. So we additionally selected 10 genes related to immune and inflammatory pathways, namely TNF, IL6, TGFB1, IL1B, IL10, IL17A, MMP9, CRP, TLR4, NLRP3 [29][30][31][32][33][34][35][36][37][38]. 342 miRNA gene pairwise scores were found using the Connection Building Method.…”
Section: Discussionmentioning
confidence: 99%